RESEARCH ON THE GEOMORPHOLOGICAL AND SEDIMENTARY FEATURES, AND THEIR RELATIONSHIP FOR IDENTIFYING TRACES OF THE ANCIENT COASTLINES ON THE CONTINENTAL SHELF FROM DA NANG TO PHAN THIET - Tuan, Tran Anh (Vietnam Journal of Marine Science and Technology, 2015)
This paper presents the research results of geomorphological and surface sedimentary features and their relationship for identifying traces of ancient coastlines on the continental shelf from Da Nang to Phan Thiet based on the analysis of survey data such as single-beam bathymetry, multi-beam bathymetry and geological samples of the study area collected in 2013. On the basis of linking the three dimensional topographic cross sections to sediment samples, the research has identified traces of the ancient coastlines located in 7 different deep levels: 20 - 25 m, 35 - 50 m, 50 - 65 m, 70 - 80 m, 90 - 130 m, 130 - 150 m, and 180 m. Each of these ancient coastlines represents a standing period of sea on the continental shelf of South Central Vietnam during Pleistocene and Holocene.